McKeown esophagectomy with concomitant median arcuate ligament release in a case of esophageal cancer with celiac artery stenosis - Keita Hanada; Shigeru Tsunoda; Satoshi Ogiso; Tatsuto Nishigori; Shigeo Hisamori; Kazutaka Obama (Surgical Case Reports)
Abstract Background The celiac artery stenosis due to compression by median arcuate ligament (MAL) has been reported in many cases of pancreaticoduodenectomy, but not in cases of esophagectomy. Recently, the celiac artery stenosis due to MAL or arteriosclerosis has been reported to be associated with the gastric tube necrosis or anastomotic leakage following Ivor–Lewis esophagectomy. Herein, we present the first reported case of esophageal cancer with celiac artery stenosis due to compression by the MAL successfully treated by McKeown esophagectomy and gastric tube reconstruction following prophylactic MAL release. Case presentation A 72-year-old female patient was referred to our department for esophagectomy. The patient had received two courses of neoadjuvant chemotherapy with 5-FU and cisplatin for T2N0M0 squamous cell carcinoma of the middle esophagus. Preoperative contrast-enhanced computed tomography (CECT) showed celiac artery stenosis due to compression by the MAL. The development of collateral arteries around the pancreatic head was observed without evidence of aneurysm formation. The patient reported no abdominal symptoms. After robot-assisted esophagectomy with mediastinal lymphadenectomy, gastric mobilization, supra-pancreatic lymphadenectomy, and preparation of the gastric tube were performed under laparotomy. Subsequently, the MAL was cut, and released to expose the celiac artery. Improved celiac artery blood flow was confirmed by decreased pulsatility index on intraoperative Doppler sonography. The operation was completed with the cervical esophagogastric anastomosis following cervical lymphadenectomy. Postoperative CECT on postoperative day 7 demonstrated increased celiac artery patency. The patient had an uncomplicated postoperative course thereafter. Conclusions Prophylactic MAL release may be considered in patients with celiac artery stenosis due to compression by the MAL on preoperative CECT for esophagectomy.